Clinical characteristics and possible drug targets in autosomal dominant spinocerebellar ataxias - Szpisjak László (CNS & NEUROLOGICAL DISORDERS-DRUG TARGETS, 2019)
The autosomal dominant spinocerebellar ataxias (SCAs) belong to a large and expanding group of neurodegenerative disorders. SCAs comprise more than 40 subtypes characterized by progressive ataxia as a common feature. The most prevalent diseases among SCAs are caused by CAG repeat expansions in the coding-region of the causative gene resulting in polyglutamine (polyQ) tract formation in the encoded protein. Unfortunately, there is no approved therapy to treat cerebellar motor dysfunction in SCA patients. In recent years, several studies have been conducted to recognize the clinical and pathophysiological aspects of the polyQ SCAs more accurately. This scientific progress has provided new opportunities to develop promising gene therapies, including RNA interference and antisense oligonucleotides.The aim of the current work is to give a brief summary of the clinical features of SCAs and to review the cardinal points of pathomechanisms of the most common polyQ SCAs. In addition, we review the last few years promising gene suppression therapies of the most frequent polyQ SCAs in animal models, on the basis of which human trials may be initiated in the near future.